Comparison Between Electroacupuncture, Detomidine Plus Electroacupuncture And Detomidine Alone For Laparoscopic Surgery In Goats - Khalifa Ashour (Journal of Applied Veterinary Sciences, 2020)
This study aimed to validate the effectiveness of electroacupuncture (EA), detomidine plus electroacupuncture and detomidine alone for laparoscopy in goats in terms of physiological variables, vital parameters, CBC and pain threshold. Fifteen healthy adult bucks divided into 3 groups (5 bucks/group); (group I) received electroacupuncture at 10 newly selected acupoints, (group II) get electroacupuncture plus detomidine and (group III) administered detomidine alone. The obtained data (M ±SD) were assessed at intervals (0 min.) before induction, (5 min.), (10 min.), (15 min.) and (20 min.) during induction, (30 min.), (45 min.) and (60 min.) throughout surgery and (24 hr) post-surgery, cortisol levels in serum at (0), (24 hr), and (72 hr) throughout laparoscopy. Group (I) showed improvement of the rates of eyelid closure, head and neck relaxation, rumen motility, and tympany. The respiratory rates, the body temperatures and capillary fill times for the three groups were not significantly different. Hematocrit, Hemoglobin, RBCs, Platelets and oxygen saturation (SpO2) were significant. ALT and AST showed no significance. Cortisol and pain threshold showed significant difference. Thus, electroacupuncture could be recommended for goat laparoscopic surgery as it works more potent and achieves sufficient abdominal anaesthesia superior to the other two regimes.